Development of a novel intelligent wireless sensor actor network for agricultural applications - Naseer Sabri Salim (School of Computer and Communication Engineering, University Malaysia Perlis, 2013)
A novel intelligent wireless sensor-actor network (IWSAN) based on Fuzzy Inference System for agricultural greenhouse climate control is presented in this research. The two most important mutual effects agricultural greenhouse climate parameters are considered which are the temperature and humidity during diurnal and nocturnal time.